Existence of Solutions for a Coupled System of Second and Fourth Order Elliptic Equations. (14th October 2014) - Wang, Fanglei
Abstract : The generalized quasilinearization technique is applied to obtain a monotone sequence of iterates converging uniformly and quadratically to a solution of a coupled system of second and fourth order elliptic equations.